Comparing the effects of swimming and running wheel on clinical symptoms and myelin basic protein in mice with experimental autoimmune encephalomyelitis - Maryam Karimian; Razieh Karimian; Behrouz Baghaiee; Mohsen Ghanbarzadeh; Abdolhamid Habibi (Journal of Shahrekord University of Medical Sciences)
Background and aims: The present investigation examines the impact of aerobic exercises, especially swimming and running wheel exercises, on the clinical manifestations and myelin basic protein (MBP) levels in mice with experimental autoimmune encephalomyelitis (EAE), an animal model for multiple sclerosis (MS). MBP is critical for the formation of myelin sheaths within the nervous system, and its deterioration is linked to the pathogenesis of MS. Methods: The sample of the study consisted of 96 female C57BL/6 mice. After the EAE induction, the mice were divided into 8 groups. The animals performed two exercise protocols. Then, the brain tissue was isolated, and levels of the mentioned variables were measured via the ELISA method using specific kits. The data were analyzed statistically using one-way ANOVA. Results: Results showed that lesion scores in both exercise protocols were lower in EAE mice than those in the control groups (P=0.001); in other words, swimming and receiving interferon-beta-1 reduced MBP degradation, but the decrease was not significant (P=0.09). Additionally, running wheels reduced MBP degradation, which was statistically significant (P=0.001). Conclusion: Results suggested that using a voluntary running wheel might be a more effective exercise program than swimming in preventing MBP degradation in the brain tissues of mice with EAE.